Targeted identification of C-type lectins in snake venom by 2DE and Western blot. (15th October 2020) - Ning, Wang; Yuanyuan, Li; Lipeng, Zhong; Xiang, Ling; Chunhong, Huang
Abstract: C-type lectins (CTL) and CTL-like proteins (snaclecs) are important toxins found in snake venom which can disrupt hemostasis by binding platelet membrane glycoproteins. Traditional identification of these toxins usually relies on an "activity-directed fractionation" approach which is very arduous. Here, we report a new method for rapid screening of these proteins in snake venom. Methods: A conserved and immunogenic peptide found in svCTLs (CTL and snaclecs) was identified by sequence alignment using DNAStar software. The peptide was de novo synthesized and conjugated to keyhole limpet hemocyanin (KLH). Rabbit antibodies were generated against the peptide by classical immunization. Deinagkistrodon acutus venom was separated by two-dimensional electrophoresis (2DE) followed by Western blot and CTLs immunodetected using the isolated polyclonal antibody. The same svCTL spots on a parallel 2DE gel were isolated and analyzed by MALDI-TOF-MS. Results: A highly conserved peptide with the sequence "KTWDDAEKFCTEQ" was identified as a common epitope in svCTLs. The polyclonal antibody against the 13aa-peptide was successfully prepared and purified. Its usefulness to detect svCTLs in D. acutus venom was tested by 2DE-WB and we determined that it positively identified all known D. acutus venom CTLs. Conclusions: Immunodetection with antibodies against KTWDDAEKFCTEQ is an efficient strategy to identify novel svCTLs in the context of a complex proteome. Highlights: A common epitope of snake venom C type lectins was predicted and validated. The antibody raised against the common epitope recognized most of C type lectins of Deinagkistrodon acutus venom. Two-dimensional electrophoresis-western blot is an useful strategy to profile specific protein family.